Similar relative aerobic contribution in high intensity running and cycling - Li, Y.; Götz, J.; Niessen, M.; Hartmann, U. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: An exponential relationship between relative aerobic contribution (WAER%) and duration in high intensity exercises was found by summarizing the corresponding investigations with various exercise models/sports (Gastin, 2001). However, the independence of WAER% on exercise model/sport was not verified. Therefore, the aim of this study was to examine the WAER% with selected exercise models (i.e. running and cycling) of high intensity. Methods: 24 adults (33±9yrs, 177±10cm, 73±11kg, 56.1±8.0ml/kg/min) from endurance sports (running, cycling, and triathlon) participated in this study with written consent. Each subject performed two maximal-4min exercises (running and cycling) on separate days with self-chosen pacing strategy. Energy contribution was calculated with the method implemented by Beneke et al. (2004), using accumulated oxygen consumption and net blood lactate production during exercise, as well as the fast component of oxygen debt during recovery. Spirometric data were registered by MetaMax 3B (Cortex Biophysic, Germany), and blood lactate was measured by Biosen S_line (EKF Diagnostic, Germany). Three-phase model was utilized to calculate the oxygen uptake kinetics in exercises (Poole & Jones, 2012). Differences in energetics between running and cycling were analyzed using paired t-tests. Results: WAER% were similar during 4-min maximal running and cycling (76.7±4.4% vs. 75.2±3.3%, p>0.05). Time constants of fast component in oxygen uptake kinetics were also similar in the two exercise models (16.2±3.7s vs. 14.5±4.8s, p>0.05). Discussion: The primary finding of this study was an approximate WAER% of 75% during 4-min maximal running and cycling, which was in line with existing reports (Gastin, 2001). It seemed that WAER% was independent of exercise model during certain duration (as 4-min in this study) of high intensity. The exponential relationship between WAER% and duration of high intensity exercise drawn from various reports (Gastin, 2001) could be applied to a given exercise model with high intensity. Similar time constants of fast component in oxygen uptake kinetics could be attributed to the involvement of similar muscles during running and cycling. Comparison of WAER% between exercise models/sports using different muscles (e.g. upper-body vs. lower-body) are needed to be investigated in the future.